Eseiści kondycji żydowskiej – po Zagładzie: Maurice Blanchot i Bogdan Dawid Wojdowski - Kuczyńska-Koschany, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The main object of the author’s reflection is the Jewish situation after the Holocaust expressed in the genre of literary essay. The thoughts of Maurice Blanchot and Bogdan Dawid Wojdowski – both prominent essayists – are taken into consideration as an example. Whereas the French writer’s reflections on the Jewish situation are part of his observations about the category of infinity, the Polish essayist’s realizations are intermingled with his own tragic fate as a Jew. Blanchot and Wojdowski wrote after the Holocaust, which is an unique turning point in history for the Jews and their diaspora as well as for the Mediterranean culture.